THEORY OF CULTURAL EVOLUTION IN THE HISTORY OF FOLKLORE STUDIES - Tyagi, Himanshi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Social sciences and Humanities scholars have long studied Folklore material from an interdisciplinary approach. The point of study has been revisited from the gateways of academic histories of these disciplines, which have thoroughly used folklore materials, although not as a primary study. It is important to note how the journey of mankind, from the basic communication to complex structures of verbal and non-verbal communication, which for a long time constituted folk material to a more advanced written literature attributing to reading materials to different disciplines based on their objectives. In this paper we study specifically how the theory of cultural evolution from anthropology corresponds with the history of folklore studies, and evolving understandings on the folk groups, their culture and material variations contributing to the dynamic approach.